Hubungan Kondisi Sarana Air Bersih dengan Kejadian Diare pada Balita di Wilayah Kerja Puskesmas Nanggalo Tahun 2020 - Kiky Meyliza Utami; Ida Rahman Burhan; Desmawati Desmawati (Fakultas Kedokteran, Universitas Andalas, 2021)
Background. Diarrhea is the second most common cause of death among children under five with an environment basis where the one of the causes is the lack of clean water facilities. Based on the data of Padang City Health Office, it was found that Nanggalo Health Center was in the third position with the highest incidence of diarrhea among children under five in 2018.Objective. This study aimed to relationship between condition of clean water facilities and the incidence of diarrhea in children under five in Nanggalo Health Center working area in 2020.Method. Research design used cross sectional study. The sample was 105 people and chose with proportionate random sampling technique. This research used questionnaires and observation sheets by interview and observation technique. The analysis used chi square test.Result. From the research showed the incidence of diarrhea in children under five was 34,3% and the unqualified clean water facilities was 14,3%. Then for bivariate analysis between condition of clean water facilities and the incidence of diarrhea in children under five showed that there was no significant relationship with p value = 0,425.Conclusion. Based on the result, in can be conclused that there was no relationship between condition of clean water facilities and the incidence of diarrhea in children under five in Nanggalo Health Center working area in 2020.